Spatial shifts in productivity of the coastal ocean over the past two decades induced by migration of the Pacific Anticyclone and Bakun's effect in the Humboldt Upwelling Ecosystem - Weidberg, Nicolas; Ospina-Alvarez, Andres; Bonicelli, Jessica; Barahona, Mario; Aiken, Christopher M.; Broitman, Bernardo R.; Navarrete, Sergio A. (Global and planetary change, 2020)
Intensification and poleward expansion of upwelling-favourable winds have been predicted as a response to anthropogenic global climate change and have recently been documented in most Eastern Boundary Upwelling Ecosystems of the world. To identify how these processes are impacting nearshore oceanographic habitats and, especially, long-term trends of primary productivity in the Humboldt Upwelling Ecosystem (HUE), we analysed time series of sea level pressure, wind stress, sea surface and atmospheric surface temperatures, and Chlorophyll-a, as a proxy for primary productivity, along 26°–36° S. Major artisanal and industrial fisheries are supported by phytoplankton productivity in this region and, therefore, identification of long-term trends and their spatial variability is critical for our ability to adapt to and to mitigate the effects of global climate change. We show that climate-induced trends in primary productivity are highly heterogeneous across the region. On the one hand, the well-documented poleward migration of the South Pacific Anticyclone (SPA) has led to decreased spring upwelling winds in the region between ca. 30° and 34° S, and to their intensification to the south. Decreased winds have produced slight increases in sea surface temperature and a pronounced and meridionally extensive decrease in surface Chlorophyll-a in this region of central Chile. To the north of 30° S, significant increases in upwelling winds, decreased SST, and enhanced chlorophyll-a concentration are observed in the nearshore. We show that this increase in upwelling-driven coastal productivity is probably produced by the increased land-sea pressure gradients (Bakun's effect) that have occurred over the past two decades north of 30° S. Thus, climate drivers along the HUE are inducing contrasting trends in oceanographic conditions and primary productivity, which can have far-reaching consequences for coastal pelagic and benthic ecosystems and lead to geographic displacements of the major fisheries. [Display omitted] •The South Pacific Anticyclone (SPA) is moving to the south of 34°S in spring.•Sea-land thermal contrast is increasing to the north of 30°S (Bakun's effect).•Upwelling and primary productivity is increasing to the north of 30°S.•In between 30 and 34°S upwelling and primary productivity decreased.•SPA displacement and Bakun's effect are caused by global warming.